Analysis of the Influence of Teaching Style on Student Learning Interest: Literature Review - Riza, Moch Dicky; Andayani, Endah Alamsari (Journal of Education Method and Learning Strategy, 2025)
In education, teacher teaching style is vital in influencing students’ learning interests. Teaching style involves teachers’ approach and methods to deliver material, interact with students, and create a conducive classroom atmosphere. This study aims to analyze the types of teaching styles used in Indonesia and their impact on students’ learning interests so that teachers and school institutions can form effective and innovative learning based on the conditions faced in Indonesia. This study uses a qualitative approach with a literature review method. Secondary data from scientific journals, books, and relevant research articles were analyzed thematically. The study results indicate that teaching styles that actively involve students, such as interactive and differentiation, significantly impact learning interest. Students who feel involved tend to be more motivated because they have a role in learning. In contrast, conventional styles focusing on one-way lectures are less effective in increasing learning interest because they limit student interaction. This study recommends that teachers develop more collaborative and interactive methods and that educational institutions provide the necessary training so that they can apply various teaching styles that are more interesting and relevant to students’ needs.